Վարչական հայեցողության ինստիտուտի բարելավման ուղիները վարչարարության սահմանադրական հիմքերի իրացման համատեքստում - Վաղարշակ Սարգսյան (ՀՀ ԳԱԱ հրատ.)
Данная статья рассмoтривает пути совершенствования института административного усмотрения в контексте реализации конституционных основ администрирования, которые могут стать гарантией осуществления принципа запрета произвола. This article studies the ways of improvement of administrative discretion institute in the context of the realization of constitutional basis of administration, which can be a guarantee of realization of arbitrariness prohibition principle.
Keywords: Law